Comparative Numerical Solution of Fractional Spline with Continuity Equations - Faraidun K. Hamasalh; Seaman S. Hamasalh (Tikrit Journal of Pure Science, 2023)
In this paper, constructed a fractional polynomial spline to compute the solution of FDEs; the spline interpolation with fractional polynomial coefficients must be constructed using the Caputo fractional derivative. For the provided spline function, error bounds were studied and a stability analysis was completed. To consider the numerical explanation for the provided method and compared, three examples were studied. The fractional spline function, which interpolates data, appears to be useful and accurate in solving unique problems, according to the research.